Clinical and Financial Impact of Ordering an Echocardiogram in Children with Left Axis Deviation on Their Electrocardiogram. (24th August 2015) - Ravi, Prasad; Ashwath, Ravi; Strainic, James; Li, Hong; Steinberg, Jon; Snyder, Christopher
Abstract: Objective: Left axis deviation (LAD) on the electrocardiogram (ECG) is associated with congenital heart disease (CHD), prompting the clinician to order further testing when evaluating a patient with this finding. The purpose is to (1) compare the physical examination (PE) by a pediatric cardiologist to echocardiogram (ECHO) findings in patients with LAD on resting ECG and (2) assess cost of performing ECHO on all patients with LAD on ECG. Design: An IRB approved, retrospective cohort study was performed on patients with LAD (QRS axis ≥0° to −90°) on ECG between 01/02 and 12/12. Inclusion criteria: age >0.25 and <18 years, non‐postoperative, and PE and ECHO by pediatric cardiologist. A decision tree model analyzed cost of ECHO in patients with LAD and normal/abnormal PE. Cost of complete ECHO (239.00) was obtained from 2014 Medicare reimbursement rates. Results: A total of 146 patients met inclusion criteria with 46.5% (68) having normal PE and ECHO, 1.4% (2) having normal PE and abnormal ECHO, 47.3% (69) having abnormal PE and ECHO, and 4.8% (7) having an abnormal PE and normal ECHO. Sensitivity and specificity of PE for detecting abnormalities in this population was 97% and 90%. Positive and negative predictive value of PE was 91% and 97.5%. In patients with normal PE, the cost to identify an ECHO abnormality was 8365, and 263 for those with abnormal PE. Conclusion: In presence of LAD on ECG, the sensitivity, specificity, and positive and negative predictive values of PE by a pediatric cardiologist are excellent at identifying CHD. Performing an ECHO on patients with LAD on ECG is only cost effective in the presence of an abnormal PE. In the presence of normal PE, there is a possibility of missing incidental structural cardiac disease in approximately 2% if an ECHO is not performed.